Mixed Methods: Kompetensi dan Motivasi Kerja dalam Peningkatan Kinerja Pengurus Badan Usaha Milik Desa di Desa Parsanga Kabupaten Sumenep - Rasaili, Wilda; Lathifa Khamsi, Helmy; Nurwahyudi, Yayak (Institut Riset dan Pengembangan Indonesia, 2022)
This article seeks to explain the influence of competence and work motivation on the performance of BUMDes Camar management in Parsanga Village, Sumenep City District, both partially and simultaneously. BUMDes as an organization that manages the economic growth of rural communities is expected to have good management performance in order to maximize the roles and functions of the organization. Performance is closely related to competence and work motivation. The method used is mixed, beginning with quantitative and continuing with qualitative. Quantitative data collection through questionnaires on 24 respondents. Data analysis techniques are multiple linear regression, t test and F test. The results of the competency variable t test (X1) have a significance level of 0.011. While the tcount value is 2.809 and ttable is 2.080 (2.809> 2.080), meaning that it has a significant effect. The results of the t-test for the variable work motivation (X2) show a significance level of 0.001. Meanwhile, the tcount is 4.063 and the ttable is 2.080 (4.063 > 2.080), meaning that it has a significant effect. F test results show a significance level of 0.000. While the value of Fcount r 18.175 and Ftable 3.44 (18.175> 3.44) means that competence and work motivation simultaneously have a positive and significant effect on performance. The coefficient of determination (R2) of 0.634 means that performance is influenced by competence and work motivation by 63.4%, the remaining 36.6% is influenced by other variables not examined in this study. Then qualitatively it shows that the importance and significance of loyalty in competence and work motivation is to maintain and foster the work enthusiasm of Camar BUMDes management.